ANALISIS KEMAMPUAN PENALARAN SISWA KELAS VI DI SD 06 BULUNGKULON DALAM MENYELESAIKAN MASALAH MATEMATIKA BERDASARKAN LANGKAH-LANGKAH POLYA - Ramadhana, Oliv Via Ani; 'Ariikah, Nala; Hidayah, Nor (Yayasan Panca Bakti Wiyata Pangandaran, 2024)
This study aims to analyzes the reasoning ability of grade VI students at SD 06 Bulung Kulon in solving mathematics problems based on Polya's stages. Using a quantitative descriptive method approach, this study involved four students who were selected based on their level of mathematical ability (low, medium, and high). Data collection was obtained through test questions given to students and interviews focused on the four stages of problem solving according to Polya: understanding the problem, planning the solution, implementing the plan, and checking the results. The results showed that students with high reasoning ability could follow all stages well, while students with medium and low ability faced difficulties at various stages. The most common errors occurred at the stage of understanding the problem and planning the solution, especially in recognizing the known information in the problem and the question and in understanding basic mathematical concepts such as GCD and LCM. This study emphasizes the importance of deep understanding and critical thinking skills in the process of solving mathematical problems, as well as the need for more attention from teachers to develop students' reasoning abilities effectively.